The influence of islamic education on traditional values in yoruba society - Busari Afeez Babatunde; Kana Safrina Rouzi; Ahmad Salim; Aida Hayani (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Busari Afeez Babatunde: The Influence of Islamic Education on Traditional Values in Yoruba Society. Master’s Program in Islamic Education (S-2 Pendidikan Agama Islam), Faculty of Tarbiya and Teacher Training, Alma Ata University, Yogyakarta. Yoruba society has experienced long-standing interaction between indigenous cultural traditions and Islamic education, which has shaped moral conduct, social norms, and communal life. However, despite the deep historical presence of Islam in Yorubaland, there remains a research gap in understanding how Islamic education specifically influences, preserves, reshapes, or negotiates traditional Yoruba values in contemporary society. This study aims to examine the major traditional values upheld in Yoruba society, describe the influence of Islamic education on the social and cultural life of the Yoruba people, and identify the factors that contribute to either harmony or tension between Islamic educational teachings and Yoruba traditional values. The research employed a qualitative research design using a descriptive and analytical approach. The population of the study consisted of Yoruba Muslim communities in Southwestern Nigeria, with 150 population comprising Islamic scholars, parents, and students selected purposively. Data were collected through in-depth interviews from 60 participants and document analysis, while data validity was ensured through triangulation. The data were analyzed thematically, guided by Berger’s Social Construction of Reality Theory, particularly the stages of externalization, objectivation, and internalization. The results reveal that Islamic education significantly reinforces core Yoruba traditional values such as festival, dressing, and moral uprightness, while reforming certain cultural practices to align with Islamic monotheism. Islamic education provides a moral framework that complements Yoruba ethical principles and supports cultural continuity amid modern challenges. The study concludes that Islamic education plays a crucial role in moral transformation and cultural preservation, fostering a balanced coexistence between faith, tradition, and modernity within Yoruba society.